SUSTAINABLE CONCEPT APPLICATION TO WASTEWATER TREATMENT IN NURI BUILDING AT Dr. M. SALAMUN BANDUNG HOSPITAL - Pynkyawati, Theresia (Journal of Architectural Research and Education, 2020)
Abstract - Inpatient Installation Room (IRNA) is a facility that is owned by each hospital, which requires a source of clean water with a large capacity and produces large amounts of wastewater as well. Wastewater in the form of gray water, black water, or special wastewater can be treated before being discharged or reused as a source of recycle water. The main elements in the concept of sustainability are â€œreduce, reuse, and recycleâ€, the concept can be applied to the building planning, one of which is the building utility system. The application of the concept of sustainability in the NURI building is found in the building wastewater treatment system (Gray water) as a source of recycle water that is used specifically for a flush on the toilet. The method used in this study is a descriptive method with a quantitative field data analysis approach, namely data on the number of building users, the capacity of clean water, wastewater, and recycle water, as well as the dimensions of the water reservoir. This study aims to determine and understand the effectiveness of the volume and use of space for reservoirs of clean water, wastewater, and recycle water by applying the concept of sustainability to the building wastewater treatment system in the building.Â Keywords â€“ Hospital, Wastewater, Recycle Water, Sustainability, NURI Building.